Endothelin regulates intermittent hypoxia‐induced lipolytic remodelling of adipose tissue and phosphorylation of hormone‐sensitive lipase. (20th January 2016) - Briançon‐Marjollet, Anne; Monneret, Denis; Henri, Marion; Hazane‐Puch, Florence; Pepin, Jean‐Louis; Faure, Patrice; Godin‐Ribuot, Diane
Abstract : Key points: Endothelin‐1 (ET‐1) is upregulated upon intermittent hypoxia and has lipolytic effects. Intermittent hypoxia induces adipose tissue lipolysis that may be mediated by ET‐1. In the present study, we show that ET‐1 is involved in adipose tissue remodelling induced by intermittent hypoxia and that phosphorylation of hormone‐sensitive lipase could be one mechanism mediating this effect. We also show that ET‐1 upregulates its own and its type A endothelin receptor expression, possibly leading to an autoactivatory loop. These results help us better understand the mechanisms of dyslipidaemia in disorders associated with intermittent hypoxia, such as obstructive sleep apnoea. Abstract: Obstructive sleep apnoea syndrome is characterized by repetitive episodes of upper airway collapse during sleep resulting in chronic intermittent hypoxia (IH). Obstructive sleep apnoea syndrome, through IH, promotes cardiovascular and metabolic disorders. Endothelin‐1 (ET‐1) secretion is upregulated by IH, and is able to modulate adipocyte metabolism. Therefore, the present study aimed to characterize the role of ET‐1 in the metabolic consequences of IH on adipose tissue in vivo and in vitro . Wistar rats were submitted to 14 days of IH‐cycles (30 s of 21% FiO2 and 30 s of 5% FiO2 ; 8 h day −1 ) or normoxia (air–air cycles) and were treated or not with bosentan, a dual type A and B endothelin receptor (ETA‐R and ETB‐R) antagonist. Bosentan treatment decreased plasma free fatty acid and triglyceride levels, and inhibited IH‐induced lipolysis in adipose tissue. Moreover, IH induced a 2‐fold increase in ET‐1 transcription and ETA‐R expression in adipose tissue that was reversed by bosentan. In 3T3‐L1 adipocytes, ET‐1 upregulated its own and its ETA‐R transcription and this effect was abolished by bosentan. Moreover, ET‐1 induced glycerol release and inhibited insulin‐induced glucose uptake. Bosentan and BQ123 inhibited these effects. Bosentan also reversed the ET‐1‐induced phosphorylation of hormone‐sensitive lipase (HSL) on Ser 660 . Finally, ET‐1‐induced lipolysis and HSL phosphorylation were also observed under hypoxia. Altogether, these data suggest that ET‐1 is involved in IH‐induced lipolysis in Wistar rats, and that upregulation of ET‐1 production and ETA‐R expression by ET‐1 itself under IH could amplify its effects. Moreover, ET‐1‐induced lipolysis could be mediated through ETA‐R and activation of HSL by Ser 660 phosphorylation. Key points: Endothelin‐1 (ET‐1) is upregulated upon intermittent hypoxia and has lipolytic effects. Intermittent hypoxia induces adipose tissue lipolysis that may be mediated by ET‐1. In the present study, we show that ET‐1 is involved in adipose tissue remodelling induced by intermittent hypoxia and that phosphorylation of hormone‐sensitive lipase could be one mechanism mediating this effect. We also show that ET‐1 upregulates its own and its type A endothelin receptor expression, possibly leading to an autoactivatory loop. These results help us better understand the mechanisms of dyslipidaemia in disorders associated with intermittent hypoxia, such as obstructive sleep apnoea.